1996
DOI: 10.1097/00043764-199603000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Explant Culture, Immunofluorescence and Electron-Microscopic Study of Flexor Retinaculum in Carpal Tunnel Syndrome

Abstract: Although flexor-retinaculum (FR) release provides dramatic relief from carpal tunnel syndrome (CTS), the role of this ligament in CTS is not well understood. We have adopted a unique approach to study the cellular pathogenesis of CTS by establishing a method for the culture of cells of FR from subjects with and without CTS. The cultured cells were characterized by light, immunofluorescence, electron microscopy, Western blot analysis, and growth studies. Two main differences between the CTS and control cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…There are inconsistencies regarding whether or not thickening of the TCL occurs in CTS patients with some studies noting evident thickening [7, 11, 26] and others indicating no change in ligament thickness [35, 43]. Additionally, examinations of TCL samples from CTS patients have shown that some patients exhibit fibrosis [34] or cellular changes [1] within the ligament, but these findings have not been consistently confirmed [20, 31]. The current study is motivated, in large part, by such observations of TCL changes being anecdotal in nature and requiring invasive methodologies, with few studies quantitatively examining morphological and mechanical differences of the TCL among CTS patients and controls.…”
Section: Introductionmentioning
confidence: 99%
“…There are inconsistencies regarding whether or not thickening of the TCL occurs in CTS patients with some studies noting evident thickening [7, 11, 26] and others indicating no change in ligament thickness [35, 43]. Additionally, examinations of TCL samples from CTS patients have shown that some patients exhibit fibrosis [34] or cellular changes [1] within the ligament, but these findings have not been consistently confirmed [20, 31]. The current study is motivated, in large part, by such observations of TCL changes being anecdotal in nature and requiring invasive methodologies, with few studies quantitatively examining morphological and mechanical differences of the TCL among CTS patients and controls.…”
Section: Introductionmentioning
confidence: 99%
“…Imaging studies have shown that the TCLs were thickened in individuals with carpal tunnel syndrome [3]. In addition, TCLs associated with carpal tunnel syndrome have been shown to exhibit mucoid change, amyloid deposits, inflammation, fibrocartilagenous metaplasia, and faster growth of contractile cells [4,5], which may alter the mechanical properties of the ligament and create an adverse mechanical environment responsible for compression neuropathy.…”
Section: Introductionmentioning
confidence: 99%
“…The transverse carpal ligament associated with carpal tunnel syndrome has been shown to have mucoid change, amyloid deposits, inflammation, fibrocartilagenous metaplasia, faster growth of contractile cells, and altered morphology. 1,15 Eighth, mechanical compression through physical contact between the transverse carpal ligament and the median nerve causes nerve damage. 2 To date, little is known about the mechanical properties of the carpal tunnel.…”
Section: Introductionmentioning
confidence: 99%